Kesenjangan Konsep dan Praktik Akad Mudharabah pada Pembiayaan Mikro: Peran Transformasi Digital di Bank Syariah Indonesia - Badriatul Mawadah; Chen Chen Aprilia Sabila (Universitas Multi Data Palembang, 2026)
This study aims to examine the gap between the normative concept and operational practice of mudharabah contracts in microfinance at Bank Syariah Indonesia (BSI), as well as to analyze the role of digital transformation and sharia supervision in supporting their implementation. A qualitative descriptive approach was employed using a literature-based method, drawing on BSI annual reports (2024–2025), Islamic banking statistics from the Financial Services Authority (OJK), DSN–MUI fatwas, and relevant scholarly articles published between 2020 and 2025. The findings indicate that mudharabah funds at BSI are predominantly utilized for fund mobilization, particularly through mudharabah deposits, while their application in microfinance remains limited. Operationally, BSI’s microfinance products are largely dominated by murabahah and ijarah contracts due to risk mitigation and payment certainty considerations. Digital transformation—through online financing applications, digital profiling, real-time reporting, and early warning systems—has the potential to enhance transparency and reduce moral hazard risks. The role of the Sharia Supervisory Board (SSB) becomes increasingly strategic in ensuring sharia compliance in the digital era. This study highlights the importance of strengthening digital infrastructure and financial literacy to optimize mudharabah-based microfinance.